Kesadaran Hukum Masyarakat Dalam Rangka Pendaftaran Tanah - Ardawani Hutasoit; Diandra Joy Hutapea; Eka Mei Riska Sitepu; Eko Pranata Sinaga; Gaby Agustina Nainggolan; Richa Yohana; Ramsul Nababan (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
The purpose of this writing, namely to find out the legal awareness of the community on land registration where land certificates become an important thing for land rights, there are also factors that hinder. This type of research is Empirical legal research is a type of research that combines legal and empirical methodologies. This method involves collecting empirical evidence, such as field observations and interviews. Descriptive research is a type of research that seeks to describe accurately and precisely a phenomenon or situation. The results showed that the community has a fairly good awareness related to proof of ownership of land rights with the existence of land certificates.